Doing housework and having regular daily routine standing out as factors associate with physical function in the older people - RuiQi Li; RuiQi Li; YaLun Dai; YiWen Han; Chi Zhang; Jing Pang; Jian Li; TieMei Zhang; Ping Zeng; Ping Zeng (Frontiers Media S.A., 2023)
Background and objectivesNationwide data were used to explore factors associated with physical function in order to identify interventions that could improve and maintain physical function in the older people.MethodsThe physical function was assessed by gait speed (GS). We selected 2,677 male and 2,668 female older adults (aged ≥60) who could perform the GS test as study subjects. GS was measured by having subjects walk across and back a 10-m course. A gait speed less than 20% that of a reference population (<0.7 m/s) was used as the definition of slow gait speed (SGS). Co-morbidity, polypharmacy, medical expenses, need for care, and hospitalization were used to evaluate health status. A stepwise logistic regression model was used to determine factors associated with SGS.ResultsSGS was associated with poorer health status, higher medical cost, lower ranking on the Geriatric Depression Scale (GDS) and decreased Mini-mental State Examination (MMSE). Co-morbidity (OR = 1.81, 1.58-2.07), polypharmacy (OR = 1.47, 1.25-1.74), MMSE <24 (OR = 1.85, 1.54-2.22), and GDS ≥ 11 (OR = 1.40, 1.18-1.65) were associated with SGS. In contrast, doing housework (DHW, OR = 0.43, 0.38-0.49), having a regular daily routine (RDR, OR = 0.64, 0.45-0.91), and current alcohol consumption (OR = 0.74, 0.62-0.90) were inversely associated with SGS. DHW plus having RDR could greatly reduce the risk of SGS (OR = 0.29, 0.19-0.43).ConclusionPoor physical function is associated with poorer health status in Chinese older people. Maintaining a regular daily routine and doing some housework may be important factors that can help older people preserve their physical function.